Resource Saving Innovative Forms of the Industrial Enterprises - Lubnina, Alsu A.; Shinkevich, Marina V.; Ashmarina, Svetlana I.; Zaitseva, Natalia A.; Sayfutdinova, Guzel B.; Ishmuradova, Izida I. (International Journal of Economics and Financial Issues, 2016)
The relevance of the study is reasoned by the current economic trends which suggest that the reliability of production is possible to be provided, while preserving and enhancing of natural ecological environment, by finding of quality new, revolutionary opportunities associated with the use of resource-saving and energy-saving technologies and alternative reproducible sources of production activities, creation of favorable ecological, economic and social conditions for the accumulation and implementation of human capital. The purpose of this paper is to explore innovative forms of resource saving of the industrial enterprises, aimed at improving of the competitiveness of products, using innovative energy and resource saving technologies, minimizing the generation of waste. The leading method to the study of this problem is the modeling method that allows considering of this problem as a purposeful and organized process to improve the management of industrial enterprises. In paper gives the estimation of modern condition of mineral raw material base of hydrocarbons; scientifically substantiates recommendations on the appropriateness of innovative forms' choice of resource-saving at industrial enterprises. The practical value is in the fact that the results of the study allow better and more targeted adjusting of innovative activity of industrial enterprises through the application of innovative forms of resource saving and can be used in the framework of sector programs that are of interest for the state statistics bodies, ministries and agencies who are responsible for strategic analysis and planning. Keywords: Resource Saving, Innovation, Competitiveness, Equity Sharing of Profits. JEL Classifications: O31, P28, Q32.